Promoting Quality Inclusive Education for Children with Disabilities in Nigerian Basic Schools Through Research Data Integration - Lawal, Oluwaseun Temitope; Onojah, David Monday; Hamzat,, Baniyaminu Opeyemi (CV Media Inti Teknologi, 2025)
In order to accomplish Sustainable Development Goal (SDG) 4, which emphasizes inclusive and equitable quality education for all, inclusive education for children with disabilities is a crucial problem. The purpose of this essay is to assess the adoption of inclusive education in Nigerian basic schools and analyze the research data that is currently accessible. A systematic review was conducted by examining various empirical studies on inclusive education in Nigeria, covering policies, data availability, and implementation challenges. The findings reveal that although some data on the education of children with disabilities exist, the implementation of inclusive education in Nigeria remains significantly limited. Key issues identified include inadequate supportive facilities, insufficient teacher training on inclusive education, and the minimal utilization of assistive technologies. The study also highlights a significant disparity in the provision of inclusive education services between the northern and southern regions of Nigeria. The implications of these findings underscore the importance of integrating existing research data to develop policies that support the implementation of inclusive education at the basic education level. Collaboration among the government, educational institutions, non-governmental organizations (NGOs), and researchers is essential to improve access to and the quality of education for children with disabilities. By adopting a data-driven approach, Nigeria can accelerate progress toward SDG 4 and ensure inclusive and equitable education for all children